(untitled) (Archives of Criminology, 2010)
The article is a result of file examination and attempts to characterise acts related to trading in influence and their criminal evaluation formulated by the courts of law in their final sentences. The empirical basis of the research are 123 criminal proceedings which resulted in valid sentences concerning passive and active trading in influence (articles 230 , and article 231 of Polish Criminal Code ). Analysed proceedings were from across the country and were decided between 1 January 2004 and 1 November 2006. The research investigated not only the court files but also public prosecution files. No files on cases discontinued or dismissed under articles providing for the indemnity of the perpetrator who informs of the crime (article 17 of Criminal Proceeding Code under article 230a of the CC) were included. The file material contained predominantly cases of passive trading in influence (article 230 of CC) consisting in, to put it simply, an obligation to take care of a matter in a public institution in return for a bribe or a promise to do so. 92 such cases were reported, 109 persons trading in influence were accused. As a result of court decisions, 78 persons were found guilty, 5 acquitted, one found partially guilty (cleared of one charge but guilty of another), and 8 cases were dismissed on conditions. Cases of active trading in influence (article 230a of CC), that is the practice of paying for someone’s influence, were much less frequent. The files included only 31 such cases, with 57 accused for paying for trading in influence. 28 cases resulted in convictions and three were dismissed on conditions. Acquittals did not occur in this group of cases. Two basic areas of study were assumed. First, a case analysis of a corruption deed of trading in influence allowed to obtain the information necessary for drafting a profile of typical perpetrators, to identify their approach (pleading guilty/not guilty) and for drafting a profile of the act of corruption itself. The latter included investigation of the means of corruption, the initiator of the corruption proposal, a catalogue of matters (contract, document, permission etc.) to be paid for, and institutions whose operation was to be interfered by trading in influence. Corruption act profile included also an attempt to investigate the promised influence (own, third parties’, actual, fictitious) and its source (family, friends, acquaintances, co-workers, other) which the passive perpetrators referred to and which the active perpetrators sought. Second, the study analysed application of provisions defining the features of the crime (articles 230 and 230a of CC). The analysis included the practice of applying the said provisions by the prosecution and the courts, as they were obliged to interpret a deed for the purpose of proceedings in legal terms and to qualify it according to provisions of law. Legitimacy of deed qualification was evaluated, particularly by the courts in their valid final verdicts.